Statistical And Simulation Analysis On Dimple Configurations Performance Of Heat Dissipation - Kasim, Mohd Shahir; Husshini, Nur Husnina Najeah; Raja Abdullah, Raja Izamshah; Mohd Shahrim, Mohammad Shah All Hafiz; Omar, Ghazali; Ganesan, Hema Nanthini; Mohd Azam, Muhamad Ammar Farhan Maula; Mohd Nawi, Mohd Al Hafiz (Penerbit Akademia Baru, 2021)
This paper presents an investigation on cooling effect and flow structure of the spherical dimple configuration during air flow on the Aluminium surface. It is prominently known that applying dimples profile causes an enhancement in heat transfer over a plain surface. A three level of Box-Behnken response surface methodology was performed to find the correlation between the input and output variables. A total of 17 different combinations of these inputs were performed throughout the experiment. The variable inputs to be investigated namely: dimple diameter of 10 - 14 mm, dimple orientation angle of 60°- 90°, and airflow velocity of 16 - 18 m/s to observe the response on the cooling time. The Aluminium block was heated to 60°C and cooled down by air flow at room temperature. The ANOVA was used to identify the significant effect of each parameter. CFD software was used as a simulation tool to analyze the flow structure and Reynolds number that associate with the heat transfer rate to support the statistical findings. Based on the result, all the input parameters are found to be significantly dominated by air flow velocity. Staggered arrangement dimple profile surface improves cooling effect by 63% over the plain flat surface. The increment in Reynolds number will increase the heat transfer which then shortening the cooling time.